Onset of Ulcerative Colitis in a Patient with Nonalcoholic Fatty Liver Disease (NAFLD): Dramatic Effect of Plant-based Diet for NAFLD. Issue 11 (27th September 2019) - Chiba, Mitsuro; Nakane, Kunio; Abe, Hitoshi; Komatsu, Masafumi; Tozawa, Haruhiko
Abstract: Nonalcoholic fatty liver disease (NAFLD) develops in ulcerative colitis (UC) and Crohn's disease. However, there is scarce reporting on the onset of UC in patients with NAFLD. A 44-year-old man was diagnosed with UC and referred to us in 2019. His height was 166.0 cm, and body weight was 86.3 kg. The waist circumference was 93.7 cm (normal range <85) and triglyceride was 751 mg/dL. These findings, in addition to hypertension, resulted in a diagnosis of metabolic syndrome. HbA1c was normal. Ultrasonography disclosed severe fatty liver. Nonalcoholic fatty liver disease was diagnosed. He underwent 12 days of educational hospitalization for UC. A lacto-ovo-semi-vegetarian diet (1400 kcal/day), a kind of plant-based diet (PBD), was provided. He lost 4 kg, which was 4.6% of his base body weight. Triglyceride and total cholesterol decreased to the normal ranges. Transaminases and γ-glutamyl transpeptidase also decreased. His body weight decreased further after discharge. Follow-up ultrasonography indicated an improvement in hepatic enlargement. The shear wave velocity decreased from 1.11 to 0.88 m/s. His soft stool became normal stool by 2 months after discharge. Records of his health checkups revealed the presence of metabolic syndrome and abnormal liver function tests already in 2015. Thus, it was concluded that UC developed in a patient with NAFLD in this case. Plant-based diet has already been shown to be effective in inflammatory bowel disease (IBD). In the present case, NAFLD parameters were dramatically improved by PBD. Whether the improvement was due to weight loss per se or due to weight loss with PBD is to be clarified. Abstract : Ulcerative colitis developed in a patient with nonalcoholic fatty liver disease (NAFLD). Plant-based diet was effective for both diseases. Parameters of NAFLD (body mass index, triglyceride, total cholesterol, transaminases, γ-glutamyl transpeptidase, and shear wave velocity) dramatically improved.